SOLAR WATER HEATING CONVECTIVE DRYER FOR DRYING MEDICAL HERBS - Sultanova, A.; Safarov, J. E.; Dadayev, G. T.; Jumayev, B. M. (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the profiles of the temperature field of the process and operating parameters of the drying of medicinal herbs. The paper substantiates the criteria for ensuring rational material temperatures by pallets and tilt angles of the approximating straight line at fixed values of the average temperature of the processed raw materials. Mathematical modeling of the drying process with a two-phase representation of the flow pattern for direct-flow and counter-current interaction of liquid and air flows without taking into account and taking into account heat consumption for evaporation has been performed. To determine the numerical values of the parameters of the mathematical model from the experimental data obtained on Matlab, a program has been developed to evaluate the minimization of the norm of the difference of vectors corresponding to the experimental and calculated temperature profiles.